Utilization of Purple Sweet Potatoes as the Main Ingredient for Processed Lubiler Products Through Digital Marketing Techniques to Train Entrepreneurship Spirits among Students - Anida Seviana; Nur Intan Malinda; Pranesti Nita; Roleana Safetri (CV. Media Inti Teknologi, 2023)
Purple sweet potato has potential as a food function, especially as an antioxidant because of its purple color and other nutritional content. This research aims to produce a Lubiler product that contains antioxidants by substituting boiled purple sweet potato with chocolate. The research results showed that the best Lubiler was produced with a maximum substitution of 100% purple sweet potato. The characteristics of the Lubiler produced include aroma, taste and texture. The addition of purple sweet potatoes increases the soft texture, taste and maturity level of purple sweet potatoes. This lubricant can be a substitute for instant snacks. This lubricant is produced in-house and is more hygienic of course, so it can maintain health because the lubricant maintains cleanliness. The technique used in the Lubiler marketing process is using Digital Marketing Techniques where the promotion of this product is done using existing social media. It is hoped that this research can foster a spirit of entrepreneurship both among students and the general public.